Managing social problems with an agency perspective - Hallgren, Fredrik; Henriksson, Mark (My University, 2020)
The transition towards electromobility is essential to reduce CO2-emissions but brings new challenges to automotive manufacturers. Cobalt, a vital metal in most batteries for electric vehicles, is associated with serious violations of human rights when it is extracted from mines in the Democratic Republic of the Congo, the largest cobalt producer in the world. The long and complex supply chain of cobalt creates agency problems for automotive manufacturers who want to address the social issues associated with cobalt as responsibility must be delegated for them to do so. It is thereby difficult for automotive manufacturers to ensure that the cobalt in their products is ethically sourced. To guide automotive manufacturers through these challenges, the aim of this thesis is to identify agency problems that affect the social sustainability in the supply chain of cobalt and explore which strategies are suitable to manage the social sustainability. The thesis was conducted as a case study at a large automotive manufacturer. The adopted methodology involved identifying and evaluating strategies based on hypotheses that were developed and refined based on data from interviews, workshops and secondary sources. This was followed by an in-depth analysis of the strategies based on agency theory, transaction cost theory and multi-tier supply chain management. The findings suggest that automotive manufacturers should choose between a strategy where they interact directly or indirectly with sub-suppliers depending on the automotive manufacturer’s risk profile and contextual factors. Firms should opt for a direct strategy if they are risk-averse towards agency problems and social sustainability but can accept an asset specificity risk. Firms with an opposite risk profile should choose an indirect strategy. The findings also indicate that firms who adopt a direct strategy should implement a supply chain transparency strategy that gives them high visibility over their supply chain while firms that use indirect strategies can have lower levels of transparency. Regardless of whether a direct or indirect strategy is adopted, firms should engage in artisanal mining and initiatives with other downstream firms. Future research is suggested to further examine how contextual factors can make it more favorable for companies to invest additional resources to improve the social sustainability of cobalt. The relationship between firm risk profile and suggested strategy should also be investigated further through more extensive empirical data.
Keywords: Social sustainability; agency theory; transaction cost theory; multi-tier supply chain management